2005
DOI: 10.1590/s0101-81752005000400016
|View full text |Cite
|
Sign up to set email alerts
|

Estratificação vertical de abelhas Euglossina (Hymenoptera, Apidae) em uma área de Mata Atlântica, Paraíba, Brasil

Abstract: Existem poucos estudos sobre distribuição vertical de insetos, principalmente de Hymenoptera Apiformes. O objetivo do presente estudo foi verificar se existe estratificação vertical entre as espécies de Euglossina em áreas de Mata Atlântica, através da comparação da riqueza, abundância e diversidade em dois estratos, sub-bosque (1,5 m) e copa (10-12 m). Para isso, foram realizadas coletas mensais na Reserva Biológica Guaribas, de maio a dezembro de 2002, utilizando seis armadilhas contendo fragrâncias artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
4
11
0
Order By: Relevance
“…In this case, behaving like a multivoltine species, it is better to live in the understory and avoid additional costs unless other constraints, such as high population density, conspecific competition, natural enemies, and others, lead them to seek another stratum, as observed in E. cordata, E. nigrita and E. pseudocingulata, species sharing both strata. Oliveira and Campos (1996), Martins and Souza (2005) and the present study showed that the canopy is the arboreal stratum with greater diversity and evenness. Furthermore, the studies on the vertical stratification of orchid bees (Roubik, 1993;Oliveira & Campos 1996;Martins & Souza, 2005;Ferreira et al, 2011) agree that the faunal composition of both strata are similar, since the forests share many species between strata, which could be called as permanent species, according to Magurran (2004).…”
Section: Faunal Compositionsupporting
confidence: 68%
See 2 more Smart Citations
“…In this case, behaving like a multivoltine species, it is better to live in the understory and avoid additional costs unless other constraints, such as high population density, conspecific competition, natural enemies, and others, lead them to seek another stratum, as observed in E. cordata, E. nigrita and E. pseudocingulata, species sharing both strata. Oliveira and Campos (1996), Martins and Souza (2005) and the present study showed that the canopy is the arboreal stratum with greater diversity and evenness. Furthermore, the studies on the vertical stratification of orchid bees (Roubik, 1993;Oliveira & Campos 1996;Martins & Souza, 2005;Ferreira et al, 2011) agree that the faunal composition of both strata are similar, since the forests share many species between strata, which could be called as permanent species, according to Magurran (2004).…”
Section: Faunal Compositionsupporting
confidence: 68%
“…This assumption is supported by the present results regarding richness, which revealed to be significantly different between the strata only when the data were analyzed per sampling month. Martins and Souza (2005), studying the vertical stratification of orchid bees in area of Atlantic Rainforest, reported that although there have been higher total abundance in the understory, no difference was found between the strata when the monthly averages were analyzed. These results reinforce the supposed above and therefore we consider that if species or individuals are much more present in one stratum throughout all or most months of the year, this should be interpreted as the preferred stratum or that more favorable to foraging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever the reasons, the fact is that El. felipei was never recorded outside ESEC Murici in any previous field study in the "Centro de Endemismo Pernambuco" (Bezerra and Martins, 2001;Martins and Souza, 2005;Milet-Pinheiro and Schlindwein, 2005;Darrault et al, 2006;Farias et al, 2007Farias et al, , 2008Moura and Schlindwein, 2009; this study). If it is true, we hypothesise that a high level of endogamy may be present in this species, one additional factor, besides (and most probably a consequence of) its restricted geographic distribution, to threaten this species.…”
Section: Conservationsupporting
confidence: 46%
“…Roubik, 2004b;Oliveira, 2006;Rasmussen and Skov, 2006;Nemésio, 2006Nemésio, , 2007Nemésio, , 2008Nemésio, , 2009Nemésio, , 2010aNemésio, , 2011bNemésio, , c, d, 2012aAyala and Engel, 2008;Bembé, 2008;Hinojosa-Díaz and Engel, 2011a, b;Hinojosa-Díaz et al, 2011Nemésio and Engel, 2012), faunistic and ecological studies in the last decade have been mainly focused on the Atlantic Forest of eastern Brazil (e.g. Bezerra and Martins, 2001;Tonhasca Júnior et al, 2002;Santos and Sofia, 2002;Martins and Souza, 2005;MiletPinheiro and Schlindwein 2005;Darrault et al, 2006;Nemésio and Silveira, 2006b, 2007a, 2010Farias et al, 2007;Farias et al 2008;Aguiar andGaglianone, 2008, 2011;Moura and Schlindwein, 2009;Nemésio, 2010bNemésio, , 2011aNemésio, , b, e, 2012cMattozo et al, 2011;Cordeiro et al, 2013;Nemésio and Vasconcelos, 2013), although a few studies have also been conducted in the Amazon Morato, 2004, 2006;StorckTonon et al, 2009;Rasmussen, 2009;Abrahamczyk et al, 2011;Nemésio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%